Long-term results of the mucosal ablation of Barrett's esophagus: efficacy and recurrence - Saligram, Shreyas (Endosc Int Open, 2015)
Background and study aims: It has been postulated that the endoscopic ablation of Barrett’s esophagus can lead to complete eradication of the disease. This study was undertaken to evaluate the efficacy of endoscopic eradication therapy for Barrett’s esophagus and the rates of recurrence of intestinal metaplasia. Patients and methods: As part of an initial randomized controlled trial, patients with nondysplastic or low grade dysplastic Barrett’s esophagus underwent mucosal ablation. Following ablation, the patients had annual surveillance endoscopies. Recurrence was defined as the presence of intestinal metaplasia after initial complete eradication had been achieved. Results: A total of 28 patients with Barrett’s esophagus were followed for a mean of 6.4 years after ablation therapy. At baseline, the majority of the patients had nondysplastic Barrett’s esophagus (79 %). Initial complete eradication of intestinal metaplasia was achieved at a mean of 4.1 months. During long-term follow-up, initial recurrence of intestinal metaplasia was seen in 14 of the 28 of patients (50 %) at a mean of 40 months, and further maintenance ablation therapy was applied. At the final follow-up, 36 % of the patients had complete eradication of intestinal metaplasia, 18 % of the patients had intestinal metaplasia, and 21 % had died of unrelated causes; invasive esophageal adenocarcinoma had developed in 1 patient. Conclusions: The long-term results of this study demonstrate a recurrence rate of 50 % after complete eradication of Barrett’s esophagus with endoscopic eradication therapy. In addition, re-recurrence (in 36 %), even after further maintenance endoscopic eradication therapy, and deaths unrelated to the disease (21 %) occurred. Complete remission of Barrett’s esophagus appears to be a difficult goal to achieve. These results call into question the role of ablation in patients with low risk Barrett’s esophagus.